2018
DOI: 10.1016/j.mex.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of tensile strength methodology for murine skin wound healing

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The healing of the primary-closed incisions was estimated through the tensile strength test. Among the variety of biomechanical methods determining the extent of skin wound recovery, the assay mentioned above stood out as one of the easiest for implementation [59].…”
Section: In Vivo Wound-healing Effectmentioning
confidence: 99%
“…The healing of the primary-closed incisions was estimated through the tensile strength test. Among the variety of biomechanical methods determining the extent of skin wound recovery, the assay mentioned above stood out as one of the easiest for implementation [59].…”
Section: In Vivo Wound-healing Effectmentioning
confidence: 99%
“…Half of the mice in the 0, 8, or 18 Gy plus incision groups were sacrificed at 30 d or at 60 d after irradiation. The tensile strength was determined across the incisions with skin from mice in each group along with control mice (no irradiation and no incision) [24].…”
Section: Local Irradiation and Incisional Skin Woundmentioning
confidence: 99%
“…In addition to the genotypic differences, pilot studies revealed a lack of feasibility to handle and process large numbers of fresh samples with a standard tensiometer. To solve this limitation, elements of a mouse skin injury model and of tools and a protocol for measurement of tensile strength were modified and validated for reproducibility [24].…”
Section: Effects Of Local or Tbi On Incisional Skin Woundsmentioning
confidence: 99%
“…Luminol is a relatively new means of quantifying reactive oxygen species (ROS) in murine wound models, 18 and differences in wound ROS with vs without NIR‐PIT would suggest a potential negative impact on wound healing. Direct measurement of wound tensile strength is another validated method of ascertaining interference in wound healing in murine models 19 . Thus, using these methods, we investigated the effects of perioperative NIR‐PIT on postoperative wound healing in a murine model of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Direct measurement of wound tensile strength is another validated method of ascertaining interference in wound healing in murine models. 19 Thus, using these methods, we investigated the effects of perioperative NIR-PIT on postoperative wound healing in a murine model of cancer.…”
mentioning
confidence: 99%